PERANCANGAN ENTERPRISE ARCHITECTURE MENGGUNAKAN FRAMEWORK TOGAF ADM PADA DINAS KOPERASI DAN UKM KOTA PEKANBARU - Susilawati Susilawati; Idria Maita; Febi Nur Salisah; Mona Fronita (Program Studi Sistem Informasi, Universitas Banten Jaya, 2025)
The advancement of information technology and information systems has a significant impact on various organizations, both in the private and government sectors. This study aims to design an enterprise architecture using the TOGAF ADM framework in the training process in the SME sector at the Cooperatives and SMEs Service. This process was chosen because it is still done manually, resulting in obstacles such as slow data management, lack of transparency, and minimal integration between work units. The study used a qualitative approach with a case study method. Data were obtained through observation, interviews, and document analysis, which were then analyzed using the TOGAF ADM stages, including the Preliminary, Architecture Vision, and Business Architecture phases. The results of the study show that the proposed architectural design can overcome the constraints of the manual training process by presenting an integrated digital solution. This solution can accelerate the training management process, increase transparency, and strengthen coordination between work units.